The Notch pathway in Metazoa: a comparative analysis across cnidarians and beyond - Lövy, Alena; Kyslík, Jiří; Picard-Sánchez, Amparo; Holzer, Astrid S; Krejčí, Alena; Fiala, Ivan (EvoDevo, 2025)
The Notch signalling pathway is a conserved regulator of cellular processes, including differentiation, proliferation, and apoptosis, across Metazoa. While its roles in bilaterians are well-characterized, the evolutionary history and functional diversification of Notch signalling in early branching metazoans, including cnidarians and parasitic cnidarians, myxozoans, remain underexplored. This study examines the presence and structural diversity of Notch pathway components across early diverging metazoan lineages, with a particular focus on Myxozoa-parasitic cnidarians characterized by extreme morphological and genomic reduction. Comparative analyses of 58 metazoan species revealed broad conservation of core Notch components, alongside losses in ctenophores, placozoans, poriferans, and cnidarians. Myxozoa retain only 14 of the 28 canonical pathway components, lacking key elements, such as MAML, Hes/Hey, and DVL. Phylogenetic analyses of Notch receptors highlight structural divergence, particularly in extracellular domains, reflecting lineage-specific variations. The phylogeny of Delta and Jagged ligands reveals an evolutionary trajectory, with Delta ligands showing early diversification within metazoans, and their structural variability has been explored, though their functional roles remain unknown. The Notch receptor was detected at the subcellular level in proliferative stages of Sphaerospora molnari through immunolocalization studies, suggesting it is active in these cells. Our findings contribute to understanding the evolution of the Notch signalling pathway, highlighting its conserved role in developmental regulation across early branching Metazoa.